Makna Tari Kain Dalam Upacara Perkawinan Masyarakat Pauh V Kecamatan Pauh Kota Padang Sumatera Barat - Harza Dena, Vhellani; Darmawati, Darmawati (FBS Universitas Negeri Padang, 2020)
This study aims to describe and analyze the meaning of Kain dance in marriage ceremony at Pauh V, Pauah district, Padang city. This is a qualitative research using a descriptive method. The object of this research was Kain dance in Pauh V community, Pauh district, Padang city. The data used in this study were primary and secondary data. The main instrument was the researcher itself and was assisted by supporting instruments such as writing instruments, cameras, and cellphones. The data were collected through literature study, observation, interview, and documentation. The data analysis was conducted by reducing the data, displaying the data, and making conclusions. The results show that Kain dance is a traditional dance which is a manifestation of the values of Pauh V community in a marriage ceremony. The instructions are given by niniak mamak (headmen) and bako (fathers’ family) as people who are responsible. This is depicted in a dance by dancers who invite the bride and groom to dance as a form of learning.Kain dance depicts a man who is married and is recognized as an adult who must have dexterity, strength, and vigilance in facing challenges in life's journey. This dance is performed in a marriage ceremony during the malakek an gala (giving a title). However, over the time, Kain dance may be performedat religious events in Pauh V Community, Pauh District.